Isaac Taylor Tichenor : The Creation of the Baptist New South - Williams, Michael E. (Michael Edward), 1960- (Book collections on Project MUSE., 2018)
"Michael E. Williams examines Tichenor's entire life and work. He documents the methodologies Tichenor used to rally Southern Baptist support around its struggling Home Mission Board, which defined the makeup of the Southern Baptist Convention and defended the territory of the Convention. Williams contends that Tichenor's role in shaping Southern Baptists as they became the largest denomination in the South was crucial in determining both the identities of the region and the SBC."--Jacket